PROFIL PENGGUNAAN OBAT PASIEN PENYAKIT KULIT DI POLIKLINIK KULIT DAN KELAMIN RSU ANUTAPURA PALU - Fani Oktaviani; Alwiyah Mukaddas; Ingrid Faustine (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Skin diseases, one type of diseases that is still very dominant occuring and becoming one public health problem in Indonesia, are caused by bacteria, viruses, fungi, parasite infestations or allergic reactions. They can be treated with various ways including topical, systemic and or intralesional routes. This study aimed to determine the drug use profile of patients with skin disease at Dermatology and Venereology Polyclinic in Anutapura General Hospital Palu using prospective method and data were descriptively presented. The results showed that from 98 patients, there was 53.06% male; 55.10% aged 41-65 years; and 27.55% housewifes and it was found that 100% of them had clinical manifestation of rash in which the most diagnosis of skin disease was Psoriasis vulgaris as much as 13.26%. Patients receiving 4-6 amount of drug variation were 68.37% that based on total frequency of the type of drugs used (381), the most class of therapy was topical corticosteroid anti-inflammatory drugs (23.10%), such as desoximetasone (18.11%); while based on frequency of the drug dosage forms (213), tablet was the most dominant one (43.19%). This results were in accordance with the Standards of Medical Care of Anutapura General Hospital Palu